Ketepatan Kebijakan Pemerintah Daerah Kabupaten Jember Menggunakan Pakta Integritas Sebagai Syarat Dalam Penyaluran Beasiswa Pendidikan - happy, Happy Trizna Wijaya (As-Shahifah : Journal of Constitutional Law and Governance, 2022)
The purpose of this reserch is to provide enlightenment related to the appropriateness of local governments that takes integrity policies in educational scholarship distribution programs. This type of research uses a broad normative or doctrinal nature, so it explains a written rule and consistency with the implementation of Rules reviewed . Local government policies use integrity pacts that need to be reviewed with PERMEN PANRB No. 49 of 2011. One of the Ministerial Regulations serves as a legal basis for Regional Governments that make policies related to the user of integrity pacts. This is a fulfillment of the best principles government according to Law no. 30 of 2014.